Work organization and work psychology theories in the context of Work from Home - A literature-based overview - Yassien Bachtal (Technische Universität Darmstadt, Forschungscenter Betriebliche Immobilienwirtschaft, 2021)
"Work from Home" is not a new phenomenon and has been discussed in the relevant literature in recent years. Nowadays, Work from Home arouses a special interest not only for researchers but also for organizations and society as a whole. Various research disciplines have investigated the effects of socio-demographic, psychographic, organizational, and real estate factors on work success such as job satisfaction and productivity. Mostly, these success variables were investigated separately. Such onedimensional approaches distort the reality; hence, a multi-dimensional approach is necessary. This paper reflects selected work organization and work psychology theories and models first. Thereafter, using the Job Demands-Resources model, a holistic model adapted to the specifics of Work from Home is developed. The model sets its focus on the prediction of job satisfaction and productivity regarding Work from Home.
Keywords: 650; Workplace; Work from Home; Job Satisfaction; Productivity; Job Demands-Resources Model; Workplace Theories